Lecturers’ Adaptability To Technological Change And Its Impact On The Teaching Process - Mardiana, Harisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The purpose of the research is to investigate the lecturers' adaptability to technological change and its impact on the teaching process. To adapt the technological change, lecturers must have attitudes to learn technology, knowledge in technology, ability, and skills to change them into qualified lecturers. The problem in Tangerang City is the lecturers have difficulty in adapting the technology, some of the lecturers unprepared in teaching and make the learning chaotic. Other lectures give many tasks and quizzes the same as the classroom's learning, and it will not achieve the learning goal. The research method is mixed methods, and the primary data is from questionnaires that give to the lecturers by Google Form. Data collection measures in 2 dimensions of lecturers’ adaptability and online teaching. The result found that 85 respondents can adapt to technological change, and for the use of online teaching, there were 87 respondents. Some of the lecturers tried to move to online teaching and learn advanced techniques. And with this research, it was shown that lecturers were ready to move to the 21-century online learning process.